Response of rice cultivars to nitrogen in upland conditions - Mingotte, Fábio Luiz Checchio [UNESP] (2013)
Against the background of a growing world population, rice (Oryza sativa L.) consumption is expected to grow faster than its production. Therefore, an appropriate question would be: how to increase productivity in the shortterm? In this respect, it becomes important the implementation of modern agricultural production systems, such as upland rice with supplemental sprinkler irrigation. Additional information is needed to maximize the available resources, with special attention given to research on the use of nitrogen. This study aimed to evaluate the agronomic performance of commercial rice cultivars with different plant characteristics in upland conditions with supplemental sprinkler irrigation, when subjected to nitrogen in topdress application at the R1 stage (panicle differentiation). The experiment was arranged in a randomized block with split plot design, with 65 treatments, consisting of the combination of 13 cultivars in the plots, and five nitrogen levels in the subplots (0, 40, 80, 120 and 160 kg ha-1), with four replications. Genetic variability was detected among rice cultivars and the agronomic performance in response to the applied nitrogen. The topdressing application of nitrogen increases, in general, the production components and grain yield in rice. Cultivars BRS Primavera, Caiapó and IAC 202 stood out for grain yield, followed by Baldo, Carnaroli, BRS Curinga and IAC 500 with lower yields.